Nuclear pore complex dysfunction drives TDP-43 pathology in ALS - O. Ramírez-Núñez; S. Rico-Ríos; P. Torres; V. Ayala; A. Fernàndez-Bernal; M. Ceron-Codorniu; P. Andrés-Benito; A. Vinyals; S. Maqsood; I. Ferrer; R. Pamplona; M. Portero-Otin (Redox Biology)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive motor neuron degeneration and pathological aggregation of TDP-43. While protein misfolding and impaired autophagy are established features, accumulating evidence highlights the nuclear pore complex (NPC)as a vulnerable, redox-sensitive hub in ALS pathogenesis. Here, we show that selective loss of NPC components, particularly the scaffold proteins NUP107 and NUP93, and FG-repeat-containing components—is a consistent finding across ALS postmortem spinal cord, SOD1^G93A and TDP-43 mutant mouse models, and human cell systems.CRISPR-mediated depletion of NUP107 in human cells triggers hallmark features of ALS pathology, including cytoplasmic TDP-43 mislocalization, increased phosphorylation, and autophagy dysfunction. Conversely, TDP-43 knockdown perturbs NPC composition, suggesting a reciprocal regulatory loop. Crucially, we demonstrate that oxidative stress exacerbated NPC subunit mislocalization and enhanced TDP-43 aggregation. Using oxime blotting and DNPH assays, we show that FG-repeat subunits of NPC were direct targets of redox-driven carbonylation, indicating that oxidative modifications compromise NPC integrity thuspotentially affecting nucleocytoplasmic transport. Our findings established NPC dysfunction as a redox-sensitive driver of TDP-43 pathology in ALS and highlight nucleocytoplasmic transport as a promising therapeutic axis. The susceptibility of long-lived NPC proteins to oxidative damage provides a mechanistic link between redox stress, proteostasis collapse, and neurodegeneration.